Does Discontinuous Involvement of a Prostatic Needle Biopsy Core by Adenocarcinoma Correlate With a Large Tumor Focus at Radical Prostatectomy?. (February 2015) - Arias-Stella, Javier A.; Varma, Kavita R.; Montoya-Cerrillo, Diego; Gupta, Nilesh S.; Williamson, Sean R.
<x xml:space="preserve">Abstract</x> When prostate needle biopsies are involved discontinuously by tumor, no consensus remains on the optimal method of tumor quantification. We investigated whether discontinuous biopsy involvement usually results from a large tumor focus or multiple small foci. Prostate needle biopsies with discontinuous tumor and corresponding whole-mounted radical prostatectomies from 2008 to 2013 were analyzed. Linear length and percentage of biopsy involvement were measured both including and subtracting the benign intervening tissue. The corresponding region of the prostatectomy specimen was evaluated for tumor size and multifocality. From over 800 biopsy sets and 400 prostatectomies performed annually, 40 patients met inclusion criteria. Excluding benign tissue, length and percentage of biopsy involvement ranged from 1 to 7 mm and 5% to 66% (median 2.5 mm, 20%), whereas including intervening tissue yielded 4 to 15.5 mm and 25% to 100%, (median 7 mm, 70%), respectively. Benign intervening tissue measured from 2 to 10.5 mm (median 3.5 mm). In 31 patients (78%), a single tumor focus was present in the corresponding region of the prostate (the dominant tumor in 25/31). In 9 patients, multiple small foci were present. Eleven patients could have been excluded from active surveillance eligibility by measuring tumor from end to end (>50% involvement), of whom only 1 met criteria for clinically insignificant cancer at prostatectomy. Discontinuous tumor in a prostate biopsy often results from a single tumor focus in the corresponding region of the prostate (78%). Therefore, we recommend that an end-to-end measurement be provided, with accompanying diagnostic comment that this often correlates with the size of a single tumor focus.